1989
DOI: 10.1080/00268948908033745
|View full text |Cite
|
Sign up to set email alerts
|

On the Photogeneration of Charge Carriers in Quasi-One-Dimensional Semiconductors: Polydiacetylene

Abstract: Experimental data are presented showing that recombination of free carriers occurs in the bulk of mm size samples of PDA-TS single crystals under steady-state excitation. The results, combined with the shape of the photocurrent i dependence on field strength, E , lead to the following conclusions: 1) the quantum yield of free carriers cp does not depend on the field strength at E < lo3 Vlcm but increases at higher E; 2) cp depends also on the diffusion length L of free carriers before recombination in the bulk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…recombination of the electron-hole (e-h) pair, the probability of the recombination depends on the total spin of the intermediate complex [10,11]. It is known that external DC magnetic field (about 1 mT) can change the probability of the e-h pair recombination if the lifetime of this pair is less than the time of spin-lattice interaction (it is about 10 À7 s for organic solids) and at the same time large enough to allow the considerable spin evolution of the pair to occur [12]. The MFSE in this case can be negative or positive and becomes saturated usually at the field less than 10 mT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…recombination of the electron-hole (e-h) pair, the probability of the recombination depends on the total spin of the intermediate complex [10,11]. It is known that external DC magnetic field (about 1 mT) can change the probability of the e-h pair recombination if the lifetime of this pair is less than the time of spin-lattice interaction (it is about 10 À7 s for organic solids) and at the same time large enough to allow the considerable spin evolution of the pair to occur [12]. The MFSE in this case can be negative or positive and becomes saturated usually at the field less than 10 mT.…”
Section: Resultsmentioning
confidence: 99%
“…2 shows the MFSE on photoconductivity of pure MEH-PPV and its blends with PbS nanoparticles. The MFSE appears at low field (less than 1 mT) that is typical to the competition between external magnetic field and hyperfine interaction (HFI) in a polaron pair [12]. The decreasing of the relative change of the photocurrent (Y-axis) at higher fields can be explained by the triplet exciton interaction with trapped electrons.…”
Section: Article In Pressmentioning
confidence: 98%
See 1 more Smart Citation
“…In order to overcome this difficulty one must consider polarons belonging to geminate pairs. The underlying mechanism was suggested earlier, [6][7][8][9][10][11][12][13] and consists in the formation of a CT exciton ͑or lowest state of a polaron pair͒ as a result of interchain electron transfer from intrachain singlet excitation. CT is possible in conjugated polymers due to the prominent overlap of -electron clouds of two neighboring polymer chains and may become more pronounced due to the presence of a defect such as a carbonyl group.…”
Section: A On the Nature Of States Responsible For Resonant Signalsmentioning
confidence: 99%
“…That is why studying them is of importance. A hypothesis about the polaron pairs in conjugated polymers was suggested first on the basis of observation of magnetic field spin effect ͑MFSE͒ on the photoconductivity of polydiacetylene 6 and poly͑arylenevinylene͒s. 7 The authors 6,7 concluded that polaron pairs can be of two types, one as interchain charge transfer excitons, and the second as distant polaron pairs bound by Coulomb attraction and recombining geminately.…”
Section: Introductionmentioning
confidence: 99%